Strategi Pengembangan Usaha Soto Ayam Asli Lamongan (Studi Kasus : Soto Ayam Lamongan Cak Kulin di Kecamatan Kaliwates Kabupaten Jember) - Maulana, Junindar Bagus; Lutfiah, Hikmatul (KUBIS, 2022)
Soto Ayam Lamongan is a typical food from the city of Lamongan, East Java which has now spread to various regions in Indonesia, one of which is in the city of Jember. The determination of the research area was carried out purposively. The sampling method is purposive sampling using 6 respondents (1 business owner, 3 consumers who have culinary knowledge, and 2 similar but advanced or developing entrepreneurs). The analytical tools used are SWOT analysis and Grand Strategy. Based on the results of research from Cak Kulin Lamongan's Original Kampung Chicken Soto business, it is necessary to have a development strategy (S-O) and from the grand strategy diagram it shows that the Lamongan Original Kampung Chicken Soto business is at point (0.311 : 0.407 ) in quadrant I which shows a profitable position by continuing to carry out an aggressive development strategy, can increase businesses that use strategy (S-O) as a strength to take existing opportunities.